2005
DOI: 10.1534/genetics.104.034124
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of RpL38 and RpL5, Two Minute Genes Located in the Centric Heterochromatin of Chromosome 2 of Drosophila melanogaster

Abstract: The Minute mutations of Drosophila melanogaster are thought to disrupt genes that encode ribosomal proteins (RPs) and thus impair ribosome function and protein synthesis. However, relatively few Minutes have been tied to distinct RP genes and more Minute loci are likely to be discovered. We have identified point mutations in RpL38 and RpL5 in a screen for factors limiting for growth of the D. melanogaster wing. Here, we present the first genetic characterization of these loci. RpL38 is located in the centric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 56 publications
7
71
1
Order By: Relevance
“…The expression of heterochromatic essential genes such as light, rolled, RpL5, RpL38, RpL15, Nipped-B and Parp is present throughout all developmental stages (Biggs et al, 1994;Rollins et al, 1999;Tulin et al, 2002;Marygold et al, 2005;Schulze et al, 2005). The same is true for fourteen predicted genes from chromosome 2 heterochromatin that we have recently analysed (F Rossi, N Corradini, R Moschetti, R Caizzi and P Dimitri, unpublished data).…”
Section: Predicted Genessupporting
confidence: 52%
See 2 more Smart Citations
“…The expression of heterochromatic essential genes such as light, rolled, RpL5, RpL38, RpL15, Nipped-B and Parp is present throughout all developmental stages (Biggs et al, 1994;Rollins et al, 1999;Tulin et al, 2002;Marygold et al, 2005;Schulze et al, 2005). The same is true for fourteen predicted genes from chromosome 2 heterochromatin that we have recently analysed (F Rossi, N Corradini, R Moschetti, R Caizzi and P Dimitri, unpublished data).…”
Section: Predicted Genessupporting
confidence: 52%
“…Thus far, at least 32 essential genes are known to map to the mitotic heterochromatin of chromosomes 2 and 3. Only a few of these, however, are sufficiently defined at the molecular level: RpL5, light, concertina, rolled, RpL38, Nipped-B, Nipped-A, Parp and RpL15 (Hilliker, 1976;Devlin et al, 1990a, b;Parks and Wieschaus, 1991;Biggs et al, 1994;Rollins et al, 1999;Tulin et al, 2002;Myster et al, 2004;Marygold et al, 2005;Schulze et al, 2005).…”
Section: Genes Resident In the Constitutive Heterochromatin Of Drosopmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nipped-B complementation group was identified by the eight Nipped-B alleles sequenced by Gause et al (2008) (see Table 1). Similarly, Marygold et al (2005) previously sequenced line NC21 showing that it is an allele of RpL38.…”
Section: Resultsmentioning
confidence: 86%
“…One of these heterochromatic loci was identified as the previously described rl gene. Two of the remaining vital loci have since been identified: Nipped-A is synonymous with the l(2) 41Ah complementation group (Rollins et al 1999) and RpL38 is synonymous with Minute(2)41A and Hilliker's (1976) l(2)41Af complementation group (Marygold et al 2005; also referred to as l(2)Ag in FlyBase). In addition, Rollins et al (1999) found the Nipped-B gene to be located in 2Rh, but how this locus fit into the data from Hilliker (1976) was unclear.…”
mentioning
confidence: 99%